Penerapan Media Pembelajaran Powtoon Dalam Meningkatkan Motivasi dan Hasil Belajar Siswa di Kelas 10 SMAS IPIEMS Surabaya: Penelitian - Ilmi Nafi’; Mohamad Arief Rafsanjani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the application of Powtoon as a learning medium to improve student motivation and learning outcomes in economics in 10th-grade students at SMAS IPIEMS Surabaya. The background of this study is low student motivation and unsatisfactory learning outcomes, primarily due to the learning media used being conventional and uninteresting. In today's digital era, students tend to be more attracted to visual and innovative media that can stimulate their attention and interest in learning. Powtoon, as an animation-based learning medium, is considered capable of presenting learning materials in an engaging, enjoyable, and easy-to-understand manner. This study used a quantitative approach with a quasi-experimental design, comparing learning outcomes and motivation levels between the experimental group using Powtoon and the control group using conventional methods. The instruments used included a learning motivation questionnaire and a learning outcome test. The analysis results showed a significant increase in student motivation and learning outcomes in the class using Powtoon. Thus, it can be concluded that the use of Powtoon is effective in improving the quality of economics learning at the secondary school level.